Insight into the catalytic mechanism of core–shell structured Ni/Ni-N/CN catalyst towards the oxidation of furfural to furancarboxylic acid. (1st June 2022) - Yu, Xin; Miao, Zuo; Wang, Huiqiang; Jia, Wenlong; Wang, Qian; Sun, Yong; Tang, Xing; Zeng, Xianhai; Yang, Shuliang; Li, Zheng; Wei, Zuo-Jun; Xu, Feng; et al.
Graphical abstract: The fabrication of core–shell structure N-doped carbon-supported nickel catalyst with enhanced O2 activation ability, hydrogen abstraction ability, and basicity presents excellent activity for the oxidation of furfural. Highlights: Heterogeneous Ni/Ni-N/CN-5 catalyst was effective for selective oxidation of furfural. 93% yield of FA was achieved with great FA formation rate of 4.13 molFA ·molNi −1 ·h −1 . The synergy Ni and Ni-N sites in Ni/Ni-N-CN-5 was responsible for furfural oxidation. The Ni-N site facilitated the O2 activation and hydrogen abstraction process. The Ni site contributed in adsorption and activation the aldehyde group in furfural. Abstract: Developing low-cost and sustainable non-noble-metal catalysts for the efficient oxidation conversion of biomass-derived furfural to high value-added chemicals has evoked considerable interest. In this contribution, we report a facile and green core–shell structure N-doped carbon-supported nickel catalyst (Ni/Ni-N/CN), which exhibits excellent activity for the oxidation of furfural and other investigated aldehydes to corresponding carboxylic acid. Based on experimental studies, the synergy of Ni and Ni-N species in Ni/Ni-N-CN boosted the outstanding catalytic efficiency. The Ni site in Ni/Ni-N-CN contributes to the adsorption and activation of the aldehyde group in furfural, while the Ni-N site provides a stronger electron transfer ability and basicity of the Ni/Ni-N/CN catalyst, thus facilitates the activation of oxygen and abstraction of hydrogen during furfural oxidation process. Remarkably, Ni/Ni-N/CN-5 offered an outstanding FA formation rate of 4.13 molFA ·molNi −1 ·h −1, which was far more than that of the ever-reported non-noble catalysts. More importantly, the as-prepared Ni/Ni-N/CN catalyst also presents great stability and reusability. The present work provides an efficient catalytic strategy toward selective oxidation reactions.